Tropical Hydrology Simulation Model 1 For Watershed Management (Trophydsim-1) - Sahid Susanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1991)
A hydrological. simulation model, named the Tripical Hidrology Simulation Model I (Trophydsim-1), was created in order to simulate the run-off processes in mountainous terrain in a tropical monsoon region. The hydrological cycles in five major land covers, i.e., forest, upland, plantations (normally tobacco areas), paddy fields, and settlements, were each analogized by a series of four storages representing interception. depression, upper. zone and lower-zone storages. A set mathematical equations expressing empirical formula as well as physical law were employed in the model. An automatic parameter optimization routine was presented. The model was applied to the Kali Progo river basin. Central Java. Indonesia. which contains five subbasins. The simulated and recorded hydrographs were in close agreement both at every transfer point of the subbasins and in three different calendar years with different land use patterns.Some hydrologic characteristics were found from application of the model. The basin, which is mainly comprised of fresh volcanic formations. is capable of storing much water and releasing it gradually as groundwater flow. Therefore. the basin provides stable low flow for irrigating paddy land, which has expanded to 40 to 60 percent of the whole basin area. with multiple cropping patterns of rice-rice-upland crops or even rice-rice-rice.The model was also applied to simulate the effect on water regime of different modes of watershed management of simply land use patterns. Five scenarios representing extreme conditions of land use and four more realistic